An Earth Ethic for a Constantly Changing World - Bellaubí, Francesc (Razón y fe, 2020)
Climate change is the quintessential manifestation of the Anthropocene. However, behind environmental disasters lay deep social injustices to which science and technology are not capable of responding holistically. The time has come to rethink old ontological and epistemological philosophical frameworks and to build an ethic for ordinary citizens, an ethic based on dialogue to recover our identity in communion with the Geosphere, an ethic that is a symbol of resistance in hope. The article examines how the concept of noosphere can support such a geoethics.
Keywords: geoethics; antrophocene; noosphere; dialogue